Fund-Supported Programs, Fiscal Policy, and Income Distribution. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1986)
This is the third in a group of three papers dealing with various aspects of Fund-supported adjustment programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet